2019
DOI: 10.1002/biot.201800438
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Scope of Enforced ATP Wasting as a Tool for Metabolic Engineering in Escherichia coli

Abstract: The targeted increase of cellular adenosine triphosphate (ATP) turnover (enforced ATP wasting) has recently been recognized as a promising tool for metabolic engineering when product synthesis is coupled with net ATP formation. The goal of the present study is to further examine and to further develop the concept of enforced ATP wasting and to broaden its scope for potential applications. In particular, considering the fermentation products synthesized by Escherichia coli under anaerobic conditions as a proxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…), the two strains expressing the three subunit genes of the E. coli F 1 -ATPase exhibit a clear increase in ATPase activity (Fig. 1 ) by 78% and 103%, respectively, which is in the range observed when overexpressing these genes directly in E. coli [ 17 ]. In contrast, the ATPase activity even decreased by 21% in the strain expressing the T. reesei F 1 -ATPase β subunit (5D- atp2 ), providing first evidence that this strain might not behave as intended.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), the two strains expressing the three subunit genes of the E. coli F 1 -ATPase exhibit a clear increase in ATPase activity (Fig. 1 ) by 78% and 103%, respectively, which is in the range observed when overexpressing these genes directly in E. coli [ 17 ]. In contrast, the ATPase activity even decreased by 21% in the strain expressing the T. reesei F 1 -ATPase β subunit (5D- atp2 ), providing first evidence that this strain might not behave as intended.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced volumetric productivity, observed despite improved product yield and partially improved specific productivities, is a well-documented effect of enforced ATP wasting as more product is made at the expense of biomass [ 11 , 17 , 18 , 37 ]. Similar as in [ 17 ], we hypothesized that this trade-off can be overcome if growth and production are separated. This was tested in a growth-decoupled (nitrogen-starved) approach in which the strains were inoculated with a higher starting OD 600 of ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the HEX1 glucose transport system has previously been studied for its importance in creating platform strains for microbial chemical production 42 . Furthermore, extra usage of ATP has been explored as a means to increase substrate uptake rates, potentially increasing product flux under low growth conditions 43 , suggesting the importance of studying alternatives to the native phosphotransferase system. The reaction THD2pp (NADP transhydrogenase) is also required to be switched on for many products.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, iJO1366* predicts increasing lactate production rates (and reduced rates for all other fermentation products) for very high glucose uptake rates, however, the net gain in growth rate for this shift is only marginal and thus probably not relevant in vivo. However, in [33] it was shown that under conditions with large fluxes in the central metabolism, lactate synthesis might become the preferred fermentation pathway, possibly due to its reduced protein costs compared to the combined action of the ethanol, acetate and formate fermentation pathways.…”
Section: Prediction Of Exchange Fluxes and Of Flux Rangesmentioning
confidence: 99%